The Scientific American brave new brain - Horstman, Judith (Jossey-Bass, 2010)
Judith Horstman presents an informative and entertaining look at the future of the brain, based on articles from Scientific American and Scientific American Mind magazines, and the work of today's visionary neuroscientists--Publisher description.